Outcomes of Rhegmatogenous Retinal Detachment Repair With Nonrestricted Postoperative Positioning. (March 2020) - Soliman, Mohamed Kamel; Nithianandan, Harrish; McDonald, Heather; Lingley, Alexander J.; Tuli, Raman
Purpose: To investigate the anatomical success rate associated with rhegmatogenous retinal detachment (RRD) repair without postoperative head positioning. Methods: Data on 182 individuals undergoing pars plana vitrectomy (PPV) with or without phacoemulsification or scleral buckle for primary RRD with intraocular tamponade were retrospectively reviewed. The primary outcome was the initial anatomical success rate. Secondary outcome measures were the change in best-corrected visual acuity and the final reattachment rate. Results: A total of 122 eyes from 122 patients who underwent RRD repair without postoperative positioning were included in this study. PPV alone was performed in 39% of cases, whereas the remaining patients had PPV combined with phacoemulsification (35%), with scleral buckle (19%), or both (7%). Inferior breaks between the 4 o'clock and 8 o'clock positions were present in 47% of cases. Primary and final anatomical success was achieved in 86% and 98% of cases, respectively. The most common cause for redetachment was proliferative vitreoretinopathy. Age and combined inferior retinal and superior breaks were predictive of recurrence in the logistic regression model. The mean baseline best-corrected visual acuity improved from 1.2 (Snellen equivalent, 20/320) to 0.76 (Snellen, 20/125) logarithm of the minimum angle of resolution after retinal reattachment ( P < .001). Conclusions: PPV combined with or without phacoemulsification or scleral buckle for primary RRD in pseudophakic eyes or those rendered pseudophakic is associated with good anatomical outcomes without restricted postoperative head positioning. Retinal detachment in eyes with combined retinal inferior and superior breaks may have a lower success rate, and whether this is due to lack of postoperative positioning needs further evaluation in prospective, controlled studies.